Legitimacy Beyond the State? - Erman, Eva. author. aut Link
XIV, 222 p.
Keywords: Combining case studies with normative theory, this book analyzes the democratic credentials of transnational actors participating in global governance, ranging from corporations and philanthropic foundations to NGOs and social movements. This leads to innovative interpretations of democratic legitimacy in a transnational context.